Structure-property relationships in barium borophosphate glasses modified with niobium oxide - Koudelka, Ladislav; Kalenda, Petr; Mošner, Petr; Montagne, Lionel; Revel, Bertrand (Elsevier Science BV, 2016)
Phosphate glasses containing a high amount of niobium oxide exhibit non-linear optical properties which make them attractive for various optical devices. This contribution is devoted to the investigation of glasses of the series (100 - x)10.5BaO-0.1B(2)O(3)-0.4P(2)O(5)]-xNb(2)O(5) with x = 0-45 and 80[0.5BaO-yB(2)O(3)-(0.5 - y)P2O5]-20Nb(2)O(5) with y = 0-0.25. The basic characteristic parameters of the prepared glasses were determined. The index of refraction of these glasses increases substantially with increasing Nb2O5 content from 1.620 to 2.007 and the glass transition temperature increases within the range of 551-704 degrees C. The glass structure was investigated by P-31, B-11 and Nb-93 NMR, and Raman spectroscopies. Raman spectra revealed that at low Nb2O5 content a strong vibrational band of isolated NbO6 octahedra dominates the spectra. New bands appear in the Raman spectra in the glasses with 30 mol% of Nb2O5 that were assigned to vibrations of Nb-O-Nb bonds interconnecting NbO6 octahedra. B-11 MAS NMR spectra reveal the dominant role of BO4 units in the glass structure. B-11 MAS NMR spectra revealed that with increasing Nb2O5 content new resonances of BO4 units appear in the spectra due to the replacement of B-O-P bonds by B-O-Nb and B-O-B bonds. With an increasing Nb2O5 content, part of the BO4 units is also converted to BO3 units. 93Nb MAS NMR spectra primarily reflect changes in the length of Nb-O bonds in the NbO6 octahedra manifested in a decreasing asymmetry of the octahedra with increasing Nb2O5 content and the formation of niobate clusters. Niobo-borophosphate glasses reveal very high chemical durability as well as high glass transition temperatures due to the replacement of weaker P-O bonds with stronger Nb-O bonds.
Relace struktura-vlastnosti v borofosfátových sklech barnatých modifikovaných oxidem niobičným
Keywords: Borophosphate glasses; Glass structure; NMR spectra; Raman spectra; Relace struktura-vlastnosti; borofosfátová skla; oxid niobičný; Ramanova spektra; NMR spektra